Investigation on the Mechanical and Thermal Insulation Properties of Hollow Microspheres/Phenolic Syntactic Foams - Jing Dai; Chao Peng; Shuyue Zhang; Shun Wu; Minxian Shi; Zhixiong Huang (Advances in Materials Science and Engineering)
Hollow microspheres are widely used in syntactic foam as a lightweight filling material. Hollow glass microspheres (HGM) and hollow phenolic microspheres (HPM) were added to the phenolic resin to prepare phenolic syntactic foams. Then the mechanical properties, thermal insulation properties, and thermal property stability of them were studied. The mechanical test result shows that the flexural strength of phenolic syntactic foam gradually decreases with the increasing volume fraction of microspheres at room temperature. When the volume fraction of HGM is 20%, the specific strength of phenolic syntactic foam can rise to 0.0334 Nm/kg. HGM reduces the density of the phenolic syntactic foam and remains at high strength. In addition, the thermal conductivity of phenolic syntactic foam decreases with the increasing volume fraction of the hollow microspheres, indicating that the microspheres can effectively improve the thermal insulation performance of the phenolic syntactic foam. Meanwhile, the thermal conductivity of phenolic syntactic foam also increases as the heat treatment temperature rises. In addition, the thermal insulation performance of phenolic syntactic foam containing HGM is better than that containing HPM. Thermal analysis experiments show that the thermal weight loss rate becomes slower as the content of HGM increases. Therefore, HGM improves the thermal stability of the containing phenolic syntactic foam. However, the HPM reduces the thermal decomposition temperature and the thermal stability of the phenolic syntactic foam. This work provides the technical basis for applying phenolic syntactic foam as a heat insulation material.